Peranan Pemimpin Dalam Peningkatan Kepuasan Kerja di Kecamatan Mandiangin Koto Selayan Kota Bukittinggi - Ayu Angraini; Bulan Shakira Efendy; Dianatul Munawarah; Handayani Nurqoriah; Irma Santi Laoli; Syamsir Syamsir (Dinasti Research, 2022)
One important aspect that influences the success of an organization in achieving its goals is the job satisfaction of employees or members of the organization, in this case the leader plays an important role in increasing job satisfaction. This study aims to analyze the role of leaders in creating and increasing job satisfaction. This research was conducted in Kec. Mandiangin Koto Selayan City of Bukittinggi. The research method used is a qualitative method which is carried out directly by observing and analyzing facts in the field. The technique for collecting data is through interviews and observation. After the data is collected, an analysis is carried out regarding the existing problems and then conclusions will be drawn about how the role of the leader in increasing job satisfaction in the Kec. Mandiangin Koto Selayan Bukittinggi. The results of research conducted in Kec. Mandiangin Koto Selayan, Bukittinggi City, shows that the level of employee job satisfaction is still classified as not good or not optimal.